Estudo de associação entre Síndrome de Tourette e genes da via Slit-Robo - Debora Marques de Miranda (2006)
Tourette syndrome (TS) is a neuropsichyatric disorder characterized by tics and familiar inheritance. Several research groups are investigating the genetic aspects of TS, however, frequently the findings are not replicated in subsequent studies. Study of gene Slit and trk-like family member 1 (SLITRK1) has shown correlation with TS in three non-related patients. The family of SLIT proteins and their receptors, the robo family, are involved in axonal guidance in the crossing over at the spinal cord. The objective of our study was to further elucidate the putative role of Slit-Robo pathway in TS. The role of SLITRK1 gene in TS remains uncertain, since only 0.6% of patients in only one study were presented with changes in this gene. We have chosen genes that are related to the Slit-Robo pathway and present in regions pointed as suspicious in linkage association studies. Among the genes selected for our study were SLIT2, SLITRK1, ROBO3 and ROBO4. Our study is based in families with one or more affected individuals. All patients were evaluated by an experienced neuropsychiatrist. To replicate Abelson et al. (2005) findings, we used DHPLC to investigate the codifing region of SLITRK1 and subsequent sequencing of altered samples. Other genes were studied with tagSNPs. All data was analized with common statistical programs, as TRANSMIT and TDT-UNPHASED. We have found mutation in the SLITRK1 gene in one TS patient. We failed to find association among ROBO3 and ROBO4 genes and TS. Our study found association among SLIT2 gene polimorfisms and TS. In conclusion, some Slit-robo pathway genes are associated with TS, reinforcing the importance of proteins and genes involved in the neurodevelopment process for future investigation